Evaluating the Effectiveness of the Lateral Intercrural Suture to Decrease the Interdomal Distance to Improve the Definition of the Nasal Tip in Primary Rhinoplasty - Soares, Caio Márcio Correia; Mocelin, Marcos; Pasinato, Rogerio; Berger, Cezar Augusto Sarraf; Grocoske, Francisco Luiz Busato; Issa, Maria Julia Abrão (International Archives of Otorhinolaryngology, 2014)
Introduction Several surgical techniques emphasizing sutures on the lower lateral cartilage have been studied by surgeons as instruments to improve nasal tip remodeling. It is already known that the domal divergence angle and its definition angle can be modified by lateral intercrural suture (LIS). Techniques for measuring these structures are not yet standardized.Objectives Assess the efficacy of LIS using polydioxanone 4–0 absorbable thread by interdomal distance and systematize the LIS technique to improve nasal tip definition.Materials and Methods This prospective study measured and analyzed interdomal distances measured preoperatively and perioperatively compared with 3- and 6-month postoperative measurements.Results LIS was efficient on reducing interdomal distances.Conclusion LIS is statistically safe and efficient and has low morbidity when utilized in patients with mild to moderate deformities, because it reduces the domal divergence angle, effectively sustaining the nasal tip.
Keywords: rhinoplasty; polydioxanone; suture techniques